BAHIA'S GEOGRAPHICAL INDICATIONS AND THE MARKED DIFFERENCES - Silva, Priscila de Jesus (2022)
This article addresses the production and circulation of meanings through discourses, in the Brazilian Intellectual Property environment, to capture the meanings produced by the records of Geographical Indications (GIs), in territories with products of territorial specificity in the State of Bahia - Brazil. The objective is to identify and analyze, through a dialogic approach between Cultural Studies and Geography, the appropriation of cultural elements that compete for the recognition and consolidation of GIs. The work is the result of research developed within the scope of the Postgraduate Program in Territorial Studies at the State University of Bahia (PROET - UNEB). Methodologically, it was found out through Critical Discourse Analysis (CDA), three-dimensional model in Fairclough (2001a, 2001b), the social and discursive practices, ideologies and intertextualities imbricated in the hegemonic discourse on GIs in Bahia. It was investigated how the cultural dimension of the territories is summoned both in the legal-technical texts of the institutionalities of the GIs, as well as in the media narratives. The results show that the discourses about GIs announce the territorial identities as holders of a determined 'tradition' and 'notoriety', but do not represent effective actions to safeguard the knowledge and cultural expressions that compose them.